Self-excitation stress luminescent material with stress discoloration characteristic and preparation method thereof
By doping Eu2+/Eu3+ or Eu2+/Sm3+ ions in calcium fluoride-based materials, the spontaneous reduction characteristics of fluoride structure fluoride are used to realize the dual luminescent center of stress luminescent materials, solving the problem of difficult to distinguish the light intensity changes of existing materials, and realizing stress visual detection and wide application.
Patent Information
- Application Number
- CN202411526130.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-07
AI Technical Summary
The light intensity changes of existing stress luminescent materials are difficult to directly distinguish through the human eye under different stresses, which limits their use in stress visualization applications.
By doping Eu2+/Eu3+ or Eu2+/Sm3+ ions in calcium fluoride-based materials, the spontaneous reduction characteristics of fluoride structure fluoride are used to control the valence ratio of the doped elements, thereby realizing the dual luminescence center of the material and achieving the purpose of visual stress detection.
The light and color change of stress luminescent materials under different stresses is realized, and can be directly distinguished by the human eye, simplifying the process of stress visual detection, and broadening its application in stress sensors, luminescent displays, lighting lamps and other fields.
Smart Images

Figure CN119570480A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to a self-excited stress luminescent material with stress color changing characteristics and a preparation method thereof. Background Art
[0002] Mechanoluminescence (ML) refers to the phenomenon that some materials emit light when mechanically stimulated. Many solid materials will produce ML during particle rupture. However, the irreversibility of rupture-induced ML limits the practical application of these materials. In 1999, Xu Chaonan's research group at the National Institute of Advanced Industrial Science and Technology in Japan first discovered and reported ZnS:Mn 2+ and SrAl2O4:Eu 2+ The two types of materials exhibit high-intensity and repeatable stress luminescence, and introduce the principles and applications of inorganic / organic stress luminescent materials, as well as the stress / strain visualization of related sensors in target structures. The current research on the development and application of ML materials is still in the exploratory stage. Although a variety of new matrices and systems of ML materials have been reported, most of them usually require radiation charging to produce and maintain stable stress luminescence.
[0003] In addition, traditional structural damage state detection mainly uses ultrasonic detection or electrochemical detection technology. These detection technologies mainly use point-by-point detection mode and are not suitable for rapid detection of the overall stress damage state of large-scale structures. In contrast, the stress-responsive luminescent sensing coating is constructed on the surface of the structure by utilizing the stress luminescence characteristics of the material, and the deformation and damage evolution are converted into intuitive and visible luminescence or color changes. The equipment structure is simple and is not limited by the scale of the structure. However, when most single-element doped stress luminescence systems are subjected to different stress stimuli, the changes in light intensity produced are difficult to be directly distinguished by the human eye. It is necessary to rely on instruments to detect the luminescence intensity to judge the magnitude of the comparative force, which limits their use in simple and convenient stress visualization applications. There are even fewer materials that can directly distinguish light color changes through the human eye and rely on light color changes to judge the magnitude of the force.
[0004] CN113403065A discloses a fluoride-based stress luminescent material, in which manganese ions and rare earth ions are co-doped into calcium fluoride. Although the luminescent material can emit light without being pre-charged with an ultraviolet lamp, the invention only mentions that the luminescent intensity of the stress luminescent material changes under different stresses, and does not explore the changes in the light color of the material under different stresses. Summary of the invention
[0005] In order to solve the technical problems existing in the above-mentioned prior art, an object of the present invention is to provide a self-excited stress luminescent material.
[0006] Another object of the present invention is to provide a method for preparing a self-excited stress luminescent material.
[0007] Another object of the present invention is to provide a stress luminescent film.
[0008] Another object of the present invention is to provide the use of self-excited stress luminescent materials in the preparation of stress sensors, luminescent displays, lighting lamps, and luminescent flexible devices.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] A self-excited stress luminescent material, the general chemical formula of which is: Ca 1-x F2:x(Eu 2+ / Eu 3+ ), wherein 0.005<x≤0.05; or its general chemical formula is: Ca 1-y-z F2:yEu 2+ / zSm 3+ , where 0<y≤0.005, 0<z≤0.010.
[0011] The present invention utilizes the spontaneous reduction property of fluorite structure fluoride to the doping element, and controls the doping amount of Eu, thereby controlling the valence state of the doped Eu or Eu 2+ / Sm 3+ ions, thereby realizing the dual luminescence center of the material; by changing the stress magnitude, the color-changing effect of the luminescent material can be achieved, and then stress visualization detection can be realized.
[0012] The self-excitation in the present invention means that the stress luminescent material can emit light under stress without charging.
[0013] Specifically, its chemical formula is: Ca 1-x F2:x(Eu 2+ / Eu 3+ ), where 0.01≤x≤0.05.
[0014] Specifically, its chemical formula is: Ca 0.995-z F2:0.005Eu 2+ / zSm 3+ , where 0.003≤z≤0.010.
[0015] A method for preparing a self-excited stress luminescent material comprises the following steps:
[0016] S1. The calcium fluoride and europium fluoride are ground and mixed evenly or the calcium fluoride, europium fluoride and samarium fluoride are ground and mixed evenly and dried to obtain a first mixture;
[0017] S2. Sintering the first mixture at 1200-1400° C. in an inert atmosphere, and grinding to obtain the self-excited stress luminescent material.
[0018] During the synthesis process in an inert atmosphere, the raw materials CaF2 and EuF3 are in the form of ions (Ca 2+ 、Eu 3+ ) exists. It replaces Ca in the CaF2 lattice. 2+ Eu 3+ Will be spontaneously reduced to Eu 2+ , the spontaneous reduction process is achieved through charge compensation. When the Eu doping concentration exceeds a certain limit and causes the lattice to change, part of the Eu 3+ It cannot spontaneously return to Eu 2+ , Eu will appear simultaneously in the stress luminescent material 2+ and Eu 3+ When the doping concentration of Eu is controlled within a small range, it can ensure that Eu 3+ Completely reduced to Eu 2+ .
[0019] Specifically, the sintering time is 4 to 8 hours.
[0020] Specifically, the inert gas is at least one of nitrogen, argon and helium.
[0021] The present invention requires the use of an inert gas. In an inert atmosphere, Eu 3+ Will be spontaneously reduced to Eu 2+ In other atmospheres, the coexistence of two valence states of europium ions cannot be obtained. Only the luminescence center of trivalent europium is detected in the samples synthesized in air, and only the luminescence center of divalent europium is detected in the samples synthesized in a reducing atmosphere.
[0022] Organic solvents can also be added during the fluoride grinding process.
[0023] The role of organic solvents is to make the solid raw materials more uniform during the physical grinding process.
[0024] Specifically, the organic solvent is at least one of ethanol, methanol and propanol.
[0025] A stress luminescent film comprises the self-excited stress luminescent material.
[0026] Specifically, the method for preparing the stress luminescent film comprises the following steps:
[0027] The self-excited stress luminescent material is mixed with PDMS and cured to form a film.
[0028] Specifically, the mass ratio of the stress luminescent material to PDMS is 1:(1-5).
[0029] According to the friction / contact electroluminescence mechanism model, when the composite material is subjected to a macroscopic mechanical load, friction or contact-separation occurs at the interface between the self-excited stress luminescent material of the present invention and the organic elastomer (PDMS), and the electric field energy generated is sufficient to induce light. This luminescence process does not require additional energy to be provided for excitation.
[0030] The present invention also protects the use of a self-excited stress luminescent material in the preparation of a stress sensor, a luminescent display, a lighting lamp, and a luminescent flexible device.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention utilizes the spontaneous reduction property of fluorite structure fluoride to the doping element, and controls the doping amount of Eu, thereby controlling the valence state of the doped Eu or Eu 2+ / Sm 3+ ions, thereby realizing the dual luminescence center of the material; by changing the stress magnitude, the color-changing effect of the luminescent material can be achieved, and then stress visualization detection can be realized.
[0033] (2) The stress luminescent material of the present invention is synthesized by a high-temperature solid-phase method, and the preparation method adopted is simple in process, controllable in conditions, and low in preparation cost.
[0034] (3) The present invention not only enriches the luminescent properties of stress luminescent materials, but also broadens their potential applications in the field of stress visualization detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 (a) XPS spectrum of the self-excited stress luminescent material in Example 1 and (b) high-resolution XPS spectrum of Eu 3d.
[0036] Figure 2 (a) is the stress luminescence spectrum of the stress luminescence film in Examples 1 to 4 (F=8N), Figure 2 (b) is the luminescence spectrum of Example 1 under different stresses.
[0037] Figure 3 (a) XPS spectrum of the self-excited stress luminescent material in Example 5 and (b) high-resolution XPS spectrum of Eu / Sm 3d.
[0038] Figure 4 (a) is the stress luminescence spectrum of the stress luminescence film in Examples 5 to 8 (F=8N), Figure 4 (b) is the luminescence spectrum of Example 5 under different stresses.
[0039] Figure 5This is a CIE 1931 color coordinate diagram of the stress luminescence of the stress luminescent film in Example 5 under different stresses. DETAILED DESCRIPTION
[0040] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.
[0041] Example 1
[0042] A self-excited stress luminescent material, whose chemical formula is Ca 0.99 F2:0.01(Eu 2+ / Eu 3+ ), the preparation method thereof comprises the following steps:
[0043] S1. Weigh 1.5459 g of calcium fluoride (CaF2) and 0.0418 g of europium fluoride (EuF3), respectively, and grind the weighed raw materials in an agate mortar for 30 minutes to obtain a first mixture;
[0044] S2. The first mixture is transferred into a corundum crucible and placed in a high-temperature tube furnace. Nitrogen (99.999% N2) is introduced into the furnace body. The mixture is heated to 1300°C at a heating rate of 5°C / min. The mixture is kept at this temperature for 6 hours. After the mixture is naturally cooled to room temperature, the sintered product is further ground and filtered through a 200-mesh sieve to obtain a self-excited stress luminescent material.
[0045] A stress luminescent film, the preparation method of which comprises the following steps:
[0046] 1.1 g of self-excited stress luminescent material was weighed and mixed with 2.2 g of PDMS. The mixed slurry was poured into a mold and placed in an oven at 70° C. for 2 h to cure to obtain a stress luminescent film.
[0047] Example 2
[0048] A self-excited stress luminescent material, whose chemical formula is Ca 0.98 F2:0.02(Eu 2+ / Eu 3+ ), the preparation method thereof is different from that of Example 1 only in that 1.5303 g of calcium fluoride and 0.0836 g of europium fluoride are weighed, and the rest is the same as that of Example 1.
[0049] Example 3
[0050] A self-excited stress luminescent material, whose chemical formula is Ca 0.97 F2:0.03(Eu2+ / Eu 3+ ), the preparation method thereof is different from that of Example 1 only in that 1.5146 g of calcium fluoride and 0.1254 g of europium fluoride are weighed, and the rest is the same as that of Example 1.
[0051] Example 4
[0052] A self-excited stress luminescent material, whose chemical formula is Ca 0.95 F2:0.05(Eu 2+ / Eu 3+ ), the preparation method thereof is different from that of Example 1 only in that 1.4834 g of calcium fluoride and 0.2090 g of europium fluoride are weighed, and the rest is the same as that of Example 1.
[0053] Example 5
[0054] A self-excited stress luminescent material, whose chemical formula is Ca 0.992 F2:0.005Eu 2+ / 0.003Sm 3+ The preparation method thereof is different from that of Example 1 only in that 1.5451 g of calcium fluoride, 0.0261 g of europium fluoride, and 0.0156 g of samarium fluoride are weighed, and the rest is the same as that of Example 1.
[0055] Example 6
[0056] A self-excited stress luminescent material, whose chemical formula is Ca 0.990 F2:0.005Eu 2+ / 0.005Sm 3+ The preparation method thereof is different from that of Example 1 only in that 1.5420 g of calcium fluoride, 0.0261 g of europium fluoride, and 0.0259 g of samarium fluoride are weighed, and the rest is the same as that of Example 1.
[0057] Example 7
[0058] A self-excited stress luminescent material, whose chemical formula is Ca 0.987 F2:0.005Eu 2+ / 0.008Sm 3+ The preparation method thereof is different from that of Example 1 only in that 1.5373 g of calcium fluoride, 0.0261 g of europium fluoride, and 0.0415 g of samarium fluoride are weighed, and the rest is the same as that of Example 1.
[0059] Example 8
[0060] A self-excited stress luminescent material, whose chemical formula is Ca 0.985 F2:0.005Eu 2+ / 0.01Sm 3+The preparation method thereof is different from that of Example 1 only in that 1.5342 g of calcium fluoride, 0.0261 g of europium fluoride, and 0.0518 g of samarium fluoride are weighed, and the rest is the same as that of Example 1.
[0061] Test Method
[0062] The stress luminescence test system was built independently by the laboratory using a spin coater, an ocean optics fiber spectrometer and other equipment. During the test, the stress luminescence film needs to be fixed to the sample table with glue in advance, and the stress luminescence test is carried out in a dark room. The spin coater can provide a rotating platform and regulate the stress applied to the surface of the stress luminescence film and the platform rotation speed. The optical signal of stress luminescence is spectrally recorded by the ocean optics fiber spectrometer.
[0063] Figure 1 The XPS spectrum of the self-excited stress luminescent material in Example 1. Based on the analysis of the Eu 3d XPS spectrum, it is confirmed that the Eu element in the luminescent material exists in both divalent and trivalent states, which is consistent with Figure 2 The information displayed by the luminescence spectrum is consistent.
[0064] Figure 2 Graphs showing the luminescence spectra of the stress luminescent films in Examples 1 to 4. Figure 2 Eu can be clearly observed in (a) 2+ 4f 6 5d 1 →4f 7 The broadband emission centered at 430nm corresponding to the transition and Eu 3+ Narrowband emission at 580, 593, 610, 627nm. Figure 2 (b) reflects the Eu under different stresses. 2+ and Eu 3+ The ML spectra of the two luminescence centers all maintain the same emission peak position. Within a certain stress range, the ML intensity increases with increasing stress. At the same time, it can be observed that there are differences in the intensity changes of the two luminescence centers.
[0065] Figure 3 is the XPS spectrum of the self-excited stress luminescent material in Example 5. Figure 3 The signal peak of (a) is fitted as follows Figure 3 As shown in (b), the results show that the signal of the europium element in the luminescent material can only be detected in the range of 1110 to 1130 eV, corresponding to the Eu 2+ It is generally believed that the signal peak in the range of 1075 to 1095 eV corresponds to Sm 3+ , and the signal peak in the range of 1095 to 1150 eV corresponds to Sm 2+Based on the above analysis, it is inferred that in Example 5, under the synthesis conditions with a low europium doping concentration (0.5% of the synthetic raw material), the doping ion detected was Eu. 2+ and Sm 3+ .
[0066] Figure 4 Graphs showing the luminescence spectra of the stress luminescent films in Examples 5 to 8. Figure 4 Eu can be clearly observed in (a) 2+ 4f 6 5d 1 →4f 7 The broadband emission centered at 430nm corresponding to the transition and the Sm 3+ Emission at 561, 604 and 650 nm. Figure 4 (b) reflects the Eu under different stresses. 2+ and Sm 3+ The ML spectra of the two luminescence centers all maintain the same emission peak position. Within a certain stress range, the ML intensity increases with increasing stress. At the same time, it can be observed that there are differences in the intensity changes of the two luminescence centers.
[0067] Figure 5 1 is a CIE 1931 color coordinate diagram of stress luminescence of the stress luminescent film under different stresses in Example 5. As the applied stress increases, the color of the stress luminescence changes from purple to dark red.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A self-excited stress luminescent material, characterized in that: Its chemical formula is: Ca 1-x F2:x(Eu 2+ / Eu 3+ ), wherein 0.005<x≤0.05; or its general chemical formula is: Ca 1-y-z F2:yEu 2+ / zSm 3+ , where 0<y≤0.005, 0<z≤0.
010.
2. The self-excited stress luminescent material according to claim 1, characterized in that: Its chemical formula is: Ca 1-x F2:x(Eu 2+ / Eu 3+ ), where 0.01≤x≤0.
05.
3. The self-excited stress luminescent material according to claim 1, characterized in that: Its chemical formula is: Ca 0.995-z F2:0.005Eu 2+ / zSm 3+ , where 0.003≤z≤0.
010.
4. A method for preparing the self-excited stress luminescent material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. The calcium fluoride and europium fluoride are ground and mixed evenly or the calcium fluoride, europium fluoride and samarium fluoride are ground and mixed evenly and dried to obtain a first mixture; S2. Sintering the first mixture at 1200-1400° C. in an inert atmosphere, and grinding to obtain the self-excited stress luminescent material.
5. The preparation method according to claim 4, characterized in that: The sintering time is 4 to 8 hours.
6. The preparation method according to claim 4, characterized in that: The inert gas is at least one of nitrogen, argon and helium.
7. A stress luminescent film, characterized in that: It comprises the self-excited stress luminescent material as claimed in any one of claims 1 to 3.
8. The stress luminescent film according to claim 7, characterized in that: The method for preparing the stress luminescent film comprises the following steps: The self-excited stress luminescent material as claimed in any one of claims 1 to 3 is mixed with PDMS and cured to form a film.
9. The stress luminescent film according to claim 8, characterized in that: The mass ratio of the stress luminescent material to PDMS is 1:(1-5).
10. Use of the self-excited stress luminescent material according to any one of claims 1 to 3 in the preparation of stress sensors, luminescent displays, lighting lamps, and luminescent flexible devices.
Citation Information
Patent Citations
Fluoride-based stress luminescent material as well as preparation method and application thereof
CN113403065A
Cited By
Heterojunction stress luminescent material and preparation method and application thereof
CN120865916A